2010
DOI: 10.2528/pierm10061707
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Microwave Cavity Loaded With Lossy Dielectric Slab by Means of Mode Matching Method and Optimization of Load Location

Abstract: Abstract-An analysis is presented by means of a mode matching method for two microwave cavities of different sizes which are fed by a TE 10 waveguide and loaded with lossy dielectric slab type material. The accuracy of the results obtained is presented together with a comparison of the results which are obtained by the HFSS numerical method. Optimization of the load location was performed in order to maximize the electrical field on the material. The principle of this optimization is based on finding the exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Recently, a mode matching method was proposed to optimise microwave heating based on theoretical analysis. 50 The principle of the optimisation was aimed at finding the existence of positions in which the reflection coefficient S 11 is the lowest. In this way, the efficiency of power in a multimode resonator can be maximised and appropriate values are assigned to position the material for microwave heating.…”
Section: Dielectric and Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a mode matching method was proposed to optimise microwave heating based on theoretical analysis. 50 The principle of the optimisation was aimed at finding the existence of positions in which the reflection coefficient S 11 is the lowest. In this way, the efficiency of power in a multimode resonator can be maximised and appropriate values are assigned to position the material for microwave heating.…”
Section: Dielectric and Magnetic Propertiesmentioning
confidence: 99%
“…It was reported that there is a quasilinear change between the reflection coefficient change and the position of the load for microwave applicators with small dimensions and a limited number of modes. 50 In comparison with theoretical predictions, an experimental optimisation method based on the use of the Levenverg-Marquartdt technique was developed to allow an efficient optimisation of 3-D microwave applicators by means of the dielectric sample relocation as a function of its complex permittivity, size, and operating frequency. 51 High-power efficiencies can be obtained provided that operating frequency is not just below TM mode (transverse magnetic mode) cutoff frequencies for the transverse dimension of the applicator.…”
Section: Dielectric and Magnetic Propertiesmentioning
confidence: 99%
“…al., 2005, Pedreno-Molina et. al., 2006, Süle and Kent, 2010. In the present study, however, the effect of material thickness, a component that has not been thoroughly examined, on the variation of the reflection coefficient was examined.…”
Section: Introductionmentioning
confidence: 89%
“…It is suggested here that monitoring of the local average field distributions E 0 (x, y, z) │ P or position-wise distribution of the absorbed microwave power Q MW (x, y, z) │ P such as presented in Figures 4C,D and 5A,B could be useful in the area of microwave applicator design. The current general framework for understanding the working of the applicator part of a microwave heating system (whether of the single-mode-type or the multimode-type) and its design optimization is based on modeling with analytical or numerical calculations [43][44][45][46][47][48][49][50] or multi-physicsbased simulations 25,[51][52][53] or using certain experimental techniques. [54][55][56][57][58] The applicator optimization is in terms of the best coupling of the magnetron output power to the applicator cavity via a short waveguide (and an isolator coupler) or for a given dielectric 'load', or the applicator dimensions being such that the reflection coefficient of the applicator is minimum at the input frequency 56,60 , or in terms of development of strategies for uniform heating of the 'load'.…”
Section: Measured Q Mw or E 0 (X Y Z) Distributionsmentioning
confidence: 99%